The histone deacetylase inhibitor panobinostat as a radiosensitiser in bladder cancer - Groselj, B (2014)
Muscle invasive bladder cancer (MIBC) has a poor prognosis. Currently, therapy consists of radical radiotherapy or cystectomy with or without chemotherapy. The average age of patients with MIBC is high and older patients are less able to tolerate surgery or chemoradiation due to their impaired physical fitness and generally poor renal function. There is an urgent need to find new treatment regimes that are both tolerable and effective. <p.the (dsb)="" (hdac)="" (hr)="" (mrn)="" (nhej),="" a="" aims="" and="" at="" bladder="" break="" cancer="" cell="" complex.<="" deacetylase="" determine="" dna="" double="" effects="" end="" for="" further="" goal="" histone="" homologous="" in="" inhibitor="" investigate="" joining="" lines,="" look="" major="" mibc,="" mre11="" nbs1="" non-homologous="" novel="" of="" on="" p="" panobinostat="" pathway="" pathways,="" predominant="" project="" proposing="" rad50="" radiosensitising="" recombination="" repair="" strand="" study="" targeted="" the="" therapy="" this="" to="" ultimate="" upstream="" were="" with=""> The HDAC inhibitor panobinostat was found to be toxic in the low nanomolar range and significant radiosensitising effects were demonstrated at doses lower than IC50 in all the bladder cell lines studied. The radiosensitising effect of panobinostat was not influenced by TP53 status, which is generally regarded as an important determinant of bladder cancer response to radiotherapy. In the “synthetic lethality” bladder cancer cell model, panobinostat predominantly targets the HR pathway, reportedly the only proficient DNA repair pathway in MIBC. HR proteins RAD51 and CtIP were downregulated upon panobinostat treatment in a dose-dependent manner. Upstream, MRE11 and NBS1 proteins were also targeted by panobinostat, with levels slightly decreased in RT112 and T24 cells and in CAL29 cells post-ionising radiation. In summary, the HDAC inhibitor panobinostat was shown to be an efficient radiosensitiser in bladder cancer cells at low toxic doses and to predominantly target the HR pathway. These findings are promising and may contribute towards establishing a novel combination therapy of panobinostat with IR for MIBC patients. </p.the>